A New Two Points Method for Identify Dominant Harmonic Disturbance Using Frequency and Phase Spectrogram - JOPRI, MOHD HATTA; abidullah, Noor Athira; goh, zai peng; Abdullah, Abdul Rahim (Federico II University, 2014)
This paper is focused on a practical new method for dominant harmonic disturbance detection implemented using phase and frequency spectrogram based on two-point method. The first measurement point is measured at the incoming of the point of common coupling while the second measurement point at the incoming of the load. After that, the data is processed with phase and frequency spectrogram. By comparing the data, the dominant harmonic disturbance can be identified clearly. The proposed method is compared with power direction method which is the earliest method normally used in commercial product. Then, simulation and experiment are conducted to verify the accuracy of the proposed method. Finally, the results show the proposed method is more accurate than power direction method. Further work is needed to investigate the performance of the proposed method by field measurement.